Avaliação histoquímica da permeabilidade dentinária, após a utilização do EDTA como auxiliar na irrigação do canal radicular - Bonetti, Márcia Maria (2008)
The present study evaluated the dentinal permeability in all extension of the root canal, after the irrigation with sodium hypochlorite associated or not with the EDTA. Fifty bovine incisors, of similar age and anatomy, were divided in five experimental groups in accordance with the related solutions that had been used: NaOCl 1% - G1, NaOCl 1% + EDTA - G2, NaOCl 5.25% - G3, NaOCl 5.25% + EDTA - G4 and distilled water - G5 (control). The teeth were cut transversally 17mm from the apex and the roots had been instrumented. The apical prepare was executed with K # 60, in 16mm and this length was determined visually moving back 1mm with K # 15 after to reach the apical forame. Later histochemical method was carried out, a reaction physicistchemistry of coloration of the dentinal structure that allows to evidence as much as irrigant solutions penetrate in the dentine, executed with sulfate cooper and rubeanic acid. After that, the transversal section of all extension of the root in a cut machine was made, getting itself cuts of 100 micrometers of thickness, in a total of approximately 16 or 18 cuts. Of these, 3 samples of each one of the regions cervical, medial and apical had been selected. The choice of the samples was made by two operators who selected the central part from the each third. The samples had been enclosed and the pigmentation area reached for the stain in dentine was quantified by morfometric analysis in optic microscope, increase of 40x. The measures gotten in millimeters, concerning the vestibular, lingual, mesial and distal of each one of the three cuts of the areas cervical, medial and apical had been analyzed. According the results, considering the experimental model used, was observed that it had prevalence of the difference of dentinal permeability between the thirds cervical, medial and apical. However, no significant difference was found between the related studied solutions. The dentinal permeability of the radicular canal appeared, therefore, following an effectiveness order of the irrigant solutions, in which relation cervical third has greater permeability that the medium and this greater that the apical, indifferent to the irrigant solution used.